5c-2d=36

Simple and best practice solution for 5c-2d=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5c-2d=36 equation:


Simplifying
5c + -2d = 36

Solving
5c + -2d = 36

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '2d' to each side of the equation.
5c + -2d + 2d = 36 + 2d

Combine like terms: -2d + 2d = 0
5c + 0 = 36 + 2d
5c = 36 + 2d

Divide each side by '5'.
c = 7.2 + 0.4d

Simplifying
c = 7.2 + 0.4d

See similar equations:

| 2logx-log(x-3)=1 | | 1/2x-1/3=2/x | | 0.2x=-3.3 | | 20+34=27+1 | | (4y+5)(3y^2-2y-4)= | | (4y+5)(3y^2-2y-4)=equation | | 4x-3(2x)-4=0 | | (2x+15)+(3x-20)+(x+15)=360 | | X(x+4)(x-3)=0 | | 10=4A-3 | | x-3=2+x | | 3x+5y+8=0 | | 2(m+3)=15 | | 9x=3x^2-4x | | -8=k/9 | | 3a-4+5a=12 | | 2y-5=3y-.12 | | 9=2*5 | | 5x+400=8x+250 | | 7x+20=4x+5 | | (a^2/5a^9/5)/a^1/5 | | 40+x=2x+30 | | 2(a+b)+2(2+b)= | | 3/4-1/2=3/4-2/4 | | -(-7+5s)=-8s+4 | | (7k^3/n)^-2 | | x^4-2y=c | | 5(3k-3)=105 | | (2k^5/n^2)^-3 | | 2(4a+5)=26 | | 13=2(w-14) | | x^(1/2)=.16 |

Equations solver categories